Diabetes mellitus type 2 in adults - Ivan I. Dedov; Marina V. Shestakova; Alexander Y. Mayorov; Minara S. Shamkhalova; Olga Yu. Sukhareva; Gagik R. Galstyan; Alla Y. Tokmakova; Tatiana V. Nikonova; Elena V. Surkova; Irina V. Kononenko; Daria N. Egorova; Lyudmila I. Ibragimova; et al. (Сахарный диабет)
Public organization “Russian Association of Endocrinologists”. Clinical guidelines.